Demonstrative Systems Are Not Affected by Contact: Evidence from Heritage Southern Italo-Romance - Silvia Terenghi (Languages, 2022)
Deictic information is present in every language; yet, there are significant differences as to how exactly such information is encoded, yielding different indexical systems across languages. The availability of cross-linguistic variation in indexical systems provides a window into the role of contact in shaping grammars: this work contributes to the discussion by investigating whether contact plays any role in determining the grammar of indexicality in heritage varieties. This study has a two-fold aim. Empirically, it investigates ternary demonstrative systems in heritage southern Italo-Romance varieties: on the basis of comprehension and production data, these systems are shown to be in the process of undergoing change. Theoretically, it underscores the insights that the combined microcontact and diachronic perspective provides for the understanding of variation and change in heritage languages: while, at face value, the elicited heritage data seem to indicate that demonstratives are affected by contact, pairwise comparisons across heritage varieties and diachronic observations lead to rejecting a plain contact-induced explanation and to conclude, instead, that deictic elements are largely unaffected by contact and that their change in heritage varieties is, rather, endogenous.